2020
DOI: 10.1159/000511622
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of Oral Microbiota Associated with Palmoplantar Pustulosis

Abstract: <b><i>Background:</i></b> Dysbiosis of oral microbiota is implicated not only in oral inflammatory lesions, but also in a variety of extraoral diseases. The etiology of palmoplantar pustulosis (PPP) remains unclear; however, it has been suggested that chronic inflammation caused by periodontopathic bacterial infection may play a role. <b><i>Objectives/Methods:</i></b> To determine whether patients with PPP have altered diversity and composition of oral microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Second, the induction of pustule formation requires neutrophil recruitment into an intraepidermal vesicle, which was not reproduced in our mouse model. The release of IL-8 and IL-36, key cytokines that mediate neutrophil recruitment, in human tonsil epithelial cells and primary NHEKs exposed to cigarette smoke was also shown to contribute to the pathogenesis of PPP 34 , as was dysbiosis of the oral microbiota 35 37 . In a previous study, our group detected a microbiome in sterile pustules of PPP 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the induction of pustule formation requires neutrophil recruitment into an intraepidermal vesicle, which was not reproduced in our mouse model. The release of IL-8 and IL-36, key cytokines that mediate neutrophil recruitment, in human tonsil epithelial cells and primary NHEKs exposed to cigarette smoke was also shown to contribute to the pathogenesis of PPP 34 , as was dysbiosis of the oral microbiota 35 37 . In a previous study, our group detected a microbiome in sterile pustules of PPP 38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, whether reactions to dental metal are causal of PPP remains controversial (Masui et al, 2019). It is hypothesized that odontogenic diseases lead to increased immune activation, which contributes to PPP (Kikuchi and Yamamoto, 2013), and that changes in oral microbiota may be relevant to PPP (Kageyama et al, 2020).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…All studies [18][19][20][21][22] were reported the PASI scores, because the heterogeneity among the studies was not significant (p = 0.001, I 2 = 78%), we chose a random-effect model. The results showed that PASI scores were significantly lower in the probiotic supplement group (SMD = −1.40, 95% Cl = −2.63 to −0.17, p < 0.00001) (Figure 3).…”
Section: Psoriasis Area and Severity Indexmentioning
confidence: 99%